'The Irish and the Jews have a good deal in common': Irish republicanism, anti-Semitism and the post-war world. Issue 165 (May 2020) - Hanley, Brian
Abstract: This article examines how anti-Semitism influenced republican politics in revolutionary Ireland. It looks at Irish republican attitudes toward Jews, including examples of anti-Semitism. Jews were a visible minority in Ireland and one that was sometimes seen as unionist politically. This article illustrates how conspiracy theories about Jewish influence sometimes featured in Irish nationalist tropes, but were far more common in British and unionist discourses regarding events in Ireland. It also shows how individual Jews took part in revolutionary activities, even as some republicans expressed suspicion about them. Outside Ireland, Irish revolutionaries interacted with Jews in several locations, particularly the United States. There was often cooperation in these settings and both groups expressed solidarity towards one another.